Star machine Farah Al Qasimi - Vali, Murtaza (The Art Gallery of Western Australia, 2023)
Titled after Farah Al Qasimi’s photograph Star Machine (2021)—a self-portrait in which the artist uses the star machine to transcend the monotony of her surroundings after two weeks of quarantine—this publication accompanies the homonymous exhibition at the Art Gallery of Western Australia, curated by Rachel Cieśla. Presenting a selection of photographs from across new and existing bodies of work, which are wrapped in found images sourced from Alibaba merchants, this book speaks to our shared aspirations for transcendence beyond our daily lives. Understanding the camera as a relational tool, Al Qasimi’s hyper-colourised and richly textured photographs focus our attention upon how we see, feel and initiate contact with people, places, or ways of being within today’s world. Published in collaboration with the Art Gallery of Western Australia and the Simon Lee Foundation Institute of Contemporary Asian Art
Impressum: This book is published on the occasion of the exhibition "Farah Al Qasimi: Star Machine" at AGWA, Perth, 4 February to 30 July 2023
Keywords: Qasimi, Farah al -- 1991-; Ausstellungskatalog -- Art Gallery of Western Australia -- 04.02.2023-30.07.2023 -- Perth, Western Australia; Bildband